1990
DOI: 10.1017/cbo9780511607691
|View full text |Cite
|
Sign up to set email alerts
|

Demystifying Mentalities

Abstract: If faraway peoples have different ideas from our own, is this because they have different mentalities? Did our remote ancestors lack logic? The notion of distinct mentalities has been used extensively by historians to describe and explain cultural diversity. Professor Lloyd rejects this psychologising talk of mentalities and proposes an alternative approach, which takes as its starting point the social contexts of communication. Discussing apparently irrational beliefs and behaviour (such as magic), he shows h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
58
0
7

Year Published

2000
2000
2016
2016

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 511 publications
(66 citation statements)
references
References 0 publications
1
58
0
7
Order By: Relevance
“…I am going to suggest that the use of reasoning is much more influenced by the immediate context than by deep seated differences between Easterners and Westerners. This suggestion is in line both with a wealth of recent work in cross--cultural psychology studying "culture as situated cognition" (Oyserman & Lee, 2007), as well with Lloyd's idea, based on historical analyses, of the primacy of context instead of mentalities (Lloyd, 1990).…”
Section: Holistic and Analytic Thinkingsupporting
confidence: 70%
See 2 more Smart Citations
“…I am going to suggest that the use of reasoning is much more influenced by the immediate context than by deep seated differences between Easterners and Westerners. This suggestion is in line both with a wealth of recent work in cross--cultural psychology studying "culture as situated cognition" (Oyserman & Lee, 2007), as well with Lloyd's idea, based on historical analyses, of the primacy of context instead of mentalities (Lloyd, 1990).…”
Section: Holistic and Analytic Thinkingsupporting
confidence: 70%
“…Geoffrey Lloyd has convincingly argued that the Chinese and the Greek thoughts are strongly overlapping (Lloyd, 1990(Lloyd, , 1996(Lloyd, , 2006(Lloyd, , 2007, and I will only give a few illustrative examples here. Before China was unified by the Qin dynasty in the 3 rd century BCE, it was composed of many states frequently at war with each other.…”
Section: Socio--cultural Argumentsmentioning
confidence: 99%
See 1 more Smart Citation
“…This damagingly simplistic dichotomy makes it hard to understand how a head of state who, by most accounts, is intelligent and honest, could have taken the "wrong" side; and even harder to understand why his views were, at the time at least, well received by large segments of the South African public (ibid.). Fassin cites (Lloyd 1990) and (Said 1978(Said , 2003 to decry 'the hasty diagnostics of irrationality', in other words the tendency of Western scholars to scientifically "explain" as irrational those representations or acts by the non-Western 'Other' that they deem reprehensible or illegitimate (op. cit.…”
Section: Mbeki Hermeneuticsmentioning
confidence: 99%
“…In addition, Lloyd (1990) suggested that compared with those organizations without workplace spirituality, 86% with workplace spirituality could grow rapidly and increase efficiency and investment profits. In fact, some studies demonstrate that when organizations encourage spirituality, they can obtain more profits (Mitroff and Denton, 1999;Turner, 1999).…”
Section: Workplace Spirituality Individual Work Efficacy and Organizmentioning
confidence: 99%